Evolutionary structural optimization in energy absorption structures. (July 2022) - de Andrade, Fábio Morais; Magalhães, Cristina Almeida
Highlights: Same topology can be obtained for different materials. Same topology obtained between the Evolutionary and Fosberg and Nilsson [12] methods. Elements partially removed under only one nodal displacement. Differences in the values ​​of the objective function and maximum force due to the lower number of displacements. Greater stability and faster non-linear analysis of finite elements under single nodal displacement. Abstract: Energy absorbing structures are employed where the collision can cause serious consequences such as injuries or fatalities and structural damage. Because they are highly nonlinear, the optimization of these structures is complex and there are few works in the scientific community. Among the various existing topological optimization methods, evolutionary structural optimization has stood out for its versatility, and can be used in different types of engineering problems. In this sense, this work aims to apply the hard-kill evolutionary method BESO (Bi-directional Evolutionary Structural Optimization) for energy absorption structures. The objective is to compare the topologies with other methods present in the literature. Two examples are made. The first to evaluate the difference in topologies using two different materials and the second to evaluate the topologies with different displacement loads. It was verified that the same topology can be obtained with different materials and also that the same topology can be obtained between the methodologies.